Bibliometric Analysis Toward to Intellectual Capital on Small Medium Enterprises (SMES) - Nanik Kustiningsih; Ardianto; Rifda Fitrianti; , Irawat Abdul; Marwan Altarawneh (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2023)
This study determines the development trend of Intellectual Capital research in SMEs published by leading journals indexed by Scopus by identifying key authors, keywords, journals that publish in IC and MSMEs and countries that write a lot of research related to it.The data analyzed consisted of 266 research publications from 1998-2020 using the VoS viewer application to discover the intellectual Capital research development bibliometric map.The findings suggest that there are two major theories related to intellectual capital in technology-based SMEs, namely resource-based view and knowledge base view, which support and complement each other